A VIEW ON THE HISTORY OF LATVIAN-FRENCH CULTURAL RELATIONS BEFORE WORLD WAR II - Počs, Kārlis (Via Latgalica, 2008)
Because of the geographic location of the Latvian and the French nations and of different trends in the development of their histories contacts between them were established relatively late. This in turn slowed down the development of their cultural relations. In this development, we can distinguish two stages: before the formation of the Latvian state (from the second half of the 19th century until 1918), and during the Latvian state until the Soviet occupation (1920–1940). The objective of this paper is to determine the place and the role of the Latvian-French cultural relations in the development of the Latvian culture before World War II. For this purpose, archive materials, memoirs, reference materials and available studies were used. For the main part of the research, the retrospective and historico-genetic methods were mostly used. The descriptive method was mainly used for sorting the material before the main analysis. The analysis of the material revealed that the first contacts of the Latvians with French culture were recorded in the second half of the 19th century via fine arts and French literature translated into Latvian. By the end of the century, these relations became more intense, only to decrease again a little in the beginning of the 20th century, especially in the field of translations of the French belles-lettres. The events of 1905 strengthened Latvian political emigration to France. The emigrants became acquainted with French culture directly, and part of them added French culture to their previous knowledge. The outcome of World War I and the revolution in Russia then shaped the ground for the formation of the Latvian state. This dramatically changed the nature and the intensity of the Latvian-French cultural relations. To the early trends in the cooperation, the sphere of education was added, with French schools in Latvia and Latvian students in France. In the sphere of culture, relations in theater, music and arts were established. It should be noted that also an official introduction of the French into Latvian art began at that time. As a matter of fact, such an introduction had already been started by Karlis Huns, Voldemars Matvejs, and Vilhelms Purvitis, who successfully participated in the Paris art exhibitions before the formation of the Latvian state. In the period of the Latvian state, artists would arrange their personal exhibitions in France, and general shows supported by the state would be arranged. The most notable of them were the following: - In 1928, the Latvian Ministry of Education supported the participation of all Latvian artists’ unions in the exhibition dedicated to the 10th anniversary of the state. General shows were organized in Warsaw, Budapest, Copenhagen, Paris, London, etc. (Jaunākās Ziņas, 1928: Nr. 262, 266); - in the summer of 1935, an exhibition of folk art from the Baltic states, including textiles, clothes, paintings, sculptures, and ceramics was opened in Paris; - the largest exhibition of Latvian artists in Paris took place from January 27 to February 28, 1939, with presidents of both states being in charge of its organization. It can be concluded that the Latvian-French cultural relations were an important factor in the development of Latvian culture, especially in the spheres of fine arts and literature until the Soviet occupation.